2013
DOI: 10.1111/jtm.12072
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Fever, Tuberculosis, Human Immunodeficiency Virus, and Hepatitis C Virus Conversion in a Group of Long‐Term Development Aid Workers

Abstract: Infection with DFV and TB occurred in this group at rates similar to that seen in other groups of long-term travelers, and screening would appear to be warranted. While none contracted HIV or HCV infection, reported behavior did put them at risk of blood- and body fluid-borne diseases. It is important that pre-assignment travel health preparation in this group focuses on strategies to minimize these risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Dengue infection risk in long-term travelers (more than 6 months) and business expatriates (those who reside in another country for occupational purposes, and will return to their country of origin after their assignment is completed) has been associated with increased duration of assignments and local epidemiology of dengue in the destination. 40 , 41 As long-term travelers to dengue endemic areas with potential occurrence of outbreaks during their assignment of > 2 years, PCVs will continue to be at increased risk for dengue and other arboviral diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue infection risk in long-term travelers (more than 6 months) and business expatriates (those who reside in another country for occupational purposes, and will return to their country of origin after their assignment is completed) has been associated with increased duration of assignments and local epidemiology of dengue in the destination. 40 , 41 As long-term travelers to dengue endemic areas with potential occurrence of outbreaks during their assignment of > 2 years, PCVs will continue to be at increased risk for dengue and other arboviral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…DENV infection risk is determined by multiple factors, including socioeconomic, behavioral, and environmental factors. There is limited information available regarding the association between the nature of the work in volunteers and other aid workers and an increased risk of DENV infection, 40 but some studies have found an increased risk of dengue with specific activities that might increase the risk for mosquito bites, like playing outdoors sports. 42 Our investigation did not find any differences in DENV infection by type of work (education versus community economic development), work conditions (indoors versus outdoors), or mosquito avoidance behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In an Israeli survey of long-term travelers (mean duration of stay, 5.3 months), the ratio of dengue fever seroconversion was 6.7 % [ 7 ]. A New Zealand survey of long-term development aid workers in Southeast Asia (mean duration of stay, 22 months) reported a dengue fever seroconversion rate of 15.1 % [ 8 ]. Although we were unable to obtain the incidence rate in our present study because the size of the population was unknown, the results of this study and others indicate that dengue fever is an infectious disease that affects expatriates in endemic areas at a high frequency.…”
Section: Discussionmentioning
confidence: 99%
“…19 In a study examining the tuberculin conversion rate in a group of long-term aid workers from New Zealand, the TB conversion rate was 1.4 per 1000 person-months. 20 Despite this rate of newly infected persons, active TB cases are very rare. 4 The average conversion rate varies among different regions and countries (Tables 35.2…”
Section: Tuberculosismentioning
confidence: 99%